Gluconobacter aidae sp. nov., an acetic acid bacteria isolated from tropical fruits in Thailand. Issue 7 (25th July 2020) - Yukphan, Pattaraporn; Charoenyingcharoen, Piyanat; Malimas, Sukunphat; Muramatsu, Yuki; Nakagawa, Yasuyoshi; Tanasupawat, Somboon; Yamada, Yuzo
Abstract : Two bacterial strains, isolates AC10 T and AC20, which were reported in a previous study on the diversity of acetic acid bacteria in Thailand, were subjected to a taxonomic study. The phylogenetic analysis based on the 16S rRNA gene sequences showed that the two isolates were located closely to the type strains of Gluconobacter oxydans and Gluconobacter roseus . However, the two isolates formed a separate cluster from the type strains of the two species. The genomic DNA of isolate AC10 T was sequenced. The assembled genomes of the isolate were analysed for average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH). The results showed that the highest ANI and dDDH values between isolate AC10 T and G. oxydans DSM 3503 T were 91.15 and 68.2 %, which are lower than the suggested values for species delineation. The genome-based tree was reconstructed and the phylogenetic lineage based on genome sequences showed that the lineage of isolate AC10 T was distinct from G. oxydans DSM 3503 T and its related species. The two isolates were distinguished from G. oxydans and their relatives by their phenotypic characteristics and MALDI-TOF profiles. Therefore, the two isolates, AC10 T (=BCC 15749 T =TBRC 11329 T =NBRC 103576 T ) and AC20 (=BCC 15759=TBRC 11330=NBRC 103579), can be assigned to an independent species within the genus Gluconobacter, and the name Gluconobacter aidae sp. nov. is proposed for the two isolates.